The essence of truth : on Plato's cave allegory and theaetetus - Martin Heidegger (Bloomsbury, 2013)
"Martin Heidegger is one of the most important and influential philosophers of the 20th Century. A major figure in the development of phenomenology, his work also profoundly influenced many of the intellectual movements that followed in his wake, from Sartre's Existentialism to Derrida's deconstructionism. Towards the Definition of Philosophy brings together two seminal lectures that mark a breakthrough moment in Heidegger's thought and introduces the major themes that he would develop in his opus Being and Time"--